The Effect of Direct Oral Anticoagulant Therapy (DOACs) on oral surgical procedures: a systematic review - Ghassan Darwish (BMC, 2023)
Abstract Background Direct oral anticoagulants (DOACs) were developed to overcome the drawbacks of oral anticoagulants. However, not much has been discussed about the perioperative management of patients on DOACs during oral surgical procedures. Thus, we aim to determine the risk of perioperative and postoperative bleeding during oral surgical procedures in patients on DOACs. Methods A detailed literature search was performed to find potentially relevant studies using the Cochrane Library, Clinical Key, ClinicalTrials.gov, Google Scholar, Ovid, ScienceDirect, and Scopus. Every article available for free in English literature for the past 10 years, between 2012 and 2022, was searched. Results A total of 2792 abstracts were selected through a search strategy across various search engines. Based on inclusion and exclusion criteria, eleven clinical studies using DOACs as anticoagulants or studies comparing patients with and without DOACs under oral surgery procedures were found. The results were inconsistent and varied, with a few studies recommending DOAC administration with the bare minimum reported complications and others finding no statistically significant difference between discontinuation or continuation of drugs, especially across basic dental procedures. Conclusion Within the limitations of the study, it can be concluded that minor oral surgical procedures are safe for patients on DOAC therapy. However, the continuation or discontinuation of DOACs in patients undergoing oral surgical procedures remains controversial and requires further studies to extrapolate the results.